Seasonal variability of lotic macroinvertebrate communities at the habitat scale demonstrates the value of discriminating fine sediment fractions in ecological assessments - Kate L. Mathers; Patrick D. Armitage; Matthew Hill; Morwenna McKenzie; Isabel Pardo; Paul J. Wood (Ecology and Evolution, 2023)
Abstract Despite lotic systems demonstrating high levels of seasonal and spatial variability, most research and biomonitoring practices do not consider seasonality when interpreting results and are typically focused at the meso‐scale (combined pool/riffle samples) rather than considering habitat patch dynamics. We therefore sought to determine if the sampling season (spring, summer and autumn) influenced observed macroinvertebrate biodiversity, structure and function at the habitat unit scale (determined by substrate composition), and if this in turn influenced the assessment of fine sediment (sand and silt) pressures. We found that biodiversity supported at the habitat level was not seasonally consistent with the contribution of nestedness and turnover in structuring communities varying seasonally. Habitat differences in community composition were evident for taxonomic communities regardless of the season but were not seasonally consistent for functional communities, and, notably, season explained a greater amount of variance in functional community composition than the habitat unit. Macroinvertebrate biodiversity supported by silt habitats demonstrated strong seasonal differences and communities were functionally comparable to sand habitats in spring and to gravel habitats in autumn. Sand communities were impoverished compared to other habitats regardless of the season. Silt habitats demonstrated a strong increase in Ephemeroptera, Plecoptera and Trichoptera (EPT) taxa and functional richness from spring into autumn, while vegetation habitats displayed a peak in EPT abundance in summer. Only silt and sand habitats demonstrated temporal variability in functional evenness suggesting that these habitats are different in terms of their resource partitioning and productivity over time compared to other habitats. Gravel and vegetation habitats appeared to be more stable over time with functional richness and evenness remaining consistent. To accurately evaluate the influence of fine sediment on lotic ecosystems, it is imperative that routine biomonitoring and scientific research discriminate between sand and silt fractions, given they support different biodiversity, particularly during summer and autumn months.